ENVIRONMENTAL MANAGEMENT AND SUSTAINABLE DEVELOPMENT IN THE CIVIL CONSTRUCTION SECTOR - José Gomes Protásio, Jason (Journal of Interdisciplinary Debates, 2023)
The civil construction sector is, historically, extremely important for the economy of a country, especially Brazil. This reality is even more intensified in the pandemic scenario, where COVID-19 negatively impacted various sectors of the economy, especially those related to non-essential activities. The general objective of the article presented here is to discuss how environmental management and the effective management of resources can enable a process of sustainability in modern organizations, especially those that work in the civil construction sector. The methodology is descriptive and qualitative and can be classified as a bibliographical research.